Existence of a weak solution to the p-Sobolev flow. (October 2018) - Nakamura, Kenta; Misawa, Masashi
Abstract: In this paper, we study a doubly nonlinear parabolic equation, called the p -Sobolev flow here, which is the classical Yamabe flow on a bounded domain in Euclidean space in the case p = 2 . We show the existence of a weak solution to the p -Sobolev flow without geometric assumptions.